AUDIT MANAJEMEN ATAS FUNGSI KEUANGAN PADA PT. PLN (PERSERO) KANTOR CABANG MAKASSAR - Astuty Hasti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
Every company has a goal is to earn a profit and stabilize the company's survival. To achieve this, the management are looking for an alternative to offset the increase in costs incurred for the company's operations. Audit Management aims to provide a report to the management form of the findings of an audit of the management control system, if the company's operations have been run efficiently, economically and effectively, with suggestions on how to correct the weaknesses found during the audit management. Finance function can be seen in terms of collecting, analyzing and monitoring data from all functional activities in the company. Therefore, the financial function in the enterprise can be used as a tool in decision making processes, such as giving instructions to increase the success of the company's strategy and can increase net income and return of capital during the period.